Immunoexpression of aortic endothelial P-selectin and serum apolipoprotein A-1 levels after administration of arabica (Coffea arabica) and robusta (Coffea canephora) coffee bean extracts: In vivo study in atherosclerosis rat model - Ekawati, Wahyu; Heriansyah, Teuku; Kamarlis, Reno K.; Purnawarman, Adi; Sofyan, Hamny; Enitan, Seyi S. (Narra Sains Indonesia, 2024)
Atherosclerosis is a leading cause of cardiovascular disease-related death worldwide. Some studies suggested that the natural ingredients in coffee may negatively affect cardiovascular diseases, while other studies indicated that coffee contains anti-inflammatory compounds that are beneficial for cardiovascular diseases. The aim of this study was to measure the expression of P-selectin in aortic endothelial cells and the level of serum apolipoprotein A-1 (ApoA-1) in an atherosclerosis rat model after the administration of arabica and robusta coffee bean extracts at mild-moderate and high doses. An experimental study was conducted with a complete randomized design using 36 adult male white rats (Rattus norvegicus) divided into six groups: negative control (NC), positive control (PC), arabica mild-moderate dose (A1), arabica high dose (A2), robusta mild-moderate dose (R1), and robusta high dose (R2). Animals were induced atherosclerosis with atherogenic feed and then were treated with arabica and robusta coffee bean extracts at two different doses for four weeks. The results showed that the expression of P-selectin in the group of rats treated with robusta coffee bean extract was lower than arabica coffee bean extract group. Rats with robusta coffee bean extract mild-moderate dose had the highest ApoA-1 levels compared to other groups significantly (p<0.05). The level of ApoA-1 was higher in both mild-moderate and high dose of robusta coffee groups compared to the negative control group (both with p<0.001). In conclusion, mild-moderate intake of robusta coffee bean extract could reduce aortic P-selectin immunoexpression and increase serum ApoA-1 levels in an atherosclerosis rat model.